2007
DOI: 10.1111/j.1365-2265.2007.03082.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral laparoscopic adrenalectomy for corticotrophin–dependent Cushing's syndrome: a review of the Mayo Clinic experience

Abstract: This study further supports the role of BLA as an effective treatment option for patients with ACTH-dependent Cushing's syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
3
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 49 publications
5
60
3
4
Order By: Relevance
“…Nevertheless, patients with Cushing syndrome submitted to adrenalectomy also showed a reduction of obesity (Chow et al 2008). In this study, MSG-obese rats submitted to adrenalectomy presented low corticosterone levels and attenuated obesity.…”
Section: Figurementioning
confidence: 76%
“…Nevertheless, patients with Cushing syndrome submitted to adrenalectomy also showed a reduction of obesity (Chow et al 2008). In this study, MSG-obese rats submitted to adrenalectomy presented low corticosterone levels and attenuated obesity.…”
Section: Figurementioning
confidence: 76%
“…13 Laparoscopic adrenalectomy was initiated by Michel Gagner in 1992 14 and it was soon established as the standard procedure for the surgical treatment of patients with unilateral adrenal diseases. The experience with laparoscopic SBA was slower to be reported and was found to have higher rate of complications compared with unilateral laparoscopic adrenalectomy, 15,16 but the overall benefits became easily apparent. Several large series of laparoscopic SBA included 30 patients 17 and 68 patients 18 reported positive outcomes and found that the procedure was safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of CD recurrence can reach 25%, 3 years after surgery (Patil et al 2008). Second and third line therapies such as a second pituitary surgery (Patil et al 2008, Fleseriu 2012, pituitary irradiation (conventional and/or stereotactic) (Estrada et al 1997, Tritos et al 2011 and bilateral adrenalectomy (Young & Thompson 2005, Assie et al 2007, Chow et al 2008, Ritzel et al 2013) have been utilized with variable results and specific complications.…”
Section: Overview Of CD Therapymentioning
confidence: 99%